Systemic Fragility And Regulatory Resilience: A Longitudinal Analysis Of Financial Fraud And Governance Failure In Indian Markets (1992–2018) - Ujjawal Anand; Prof. (Dr.) Sanjay Prakash Srivastava (Educational Administration: Theory and Practice, 2023)
The trajectory of India’s financial markets over the past three decades has been characterized by a complex interplay of rapid technological advancement and recurring systemic fraud. This research paper conducts a critical, longitudinal analysis of market integrity breaches and financial irregularities spanning the pivotal period from the economic liberalization of 1991 to the liquidity crises of the late 2010s. It meticulously examines six landmark cases: the Harshad Mehta Scam (1992), the Ketan Parekh Scam (2001), the Satyam Computer Services Fraud (2009), the NSEL Crisis (2013), the ICICI-Axis Bank Trading Scam (2018), and the IL&FS Crisis (2018). The study’s core objective is to elucidate the evolving typologies of financial crime, tracing the fundamental shift from the exploitation of physical banking loopholes and overt price manipulation in the early 1990s to sophisticated corporate governance failures, algorithmic front-running, and regulatory arbitrage in the contemporary era. For each case, the paper provides a detailed dissection of the modus operandi, quantifies the systemic impact, and rigorously evaluates the subsequent, reactive regulatory interventions by the Securities and Exchange Board of India (SEBI) and the Reserve Bank of India (RBI). The comprehensive analysis concludes that while regulatory frameworks have demonstrably gained strength and sophistication, the continuous mutation of financial fraud- often outpacing legislative action- demands a proactive, integrated, and technology-driven surveillance and enforcement paradigm to ensure enduring market resilience and global confidence.